Dampak Bukaan Cahaya Alami Bagian Atas terhadap Kenyamanan Visual dan Termal Rumah Tinggal Dempet - Bhanu Rizfa Hakim; Feliksdinata Pangasih; Nur Husniah Thamrin (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Housing is one of the 3 primary human needs, namely clothing, food and shelter. The development of residential houses is growing rapidly with various types, one of which is a couple or attached type of residence developed by housing developers. Couple residences generally do not have side openings and only use natural light sources from the front and back of the house. These problems make the owner make a solution for opening the upper natural lighting with the aim of optimizing the entry of sunlight during the day so that there is no need for additional energy to illuminate the room. The next problem from the application of top light openings is that the light consumed by the space will be excessive and cause heat in the space. This research method is measuring the value of incoming light using a lux meter and measuring temperature and heat envelopes using a thermal camera with the hope that the measurement results are able to create the right top light opening so that it does not cause glare and does not increase heat in the room.